Sustainable futures in the built environment to 2050 a foresight approach to construction and development - Dixon, Timothy J. 1958-; Connaughton, John E.; Green, Stuart 1958- (Wiley-Blackwell, 2018)
"Brings together leading thinking on issues of new professional practice and on the future of a sustainable built environment. This book focuses on both construction and development issues, and examines how we can transition to a sustainable future by the year 2050-bringing together leading research and practice at building, neighbourhood, and city levels. It deftly analyses how emerging socio-economic, technological, and environmental trends will influence the built environment of the future. The book covers a broad spectrum of interests across the scales of buildings, communities and cities, including how professional practice will need to adapt to these trends. The broader context is provided by an analysis of emergent business models and the changing requirements for expert advice from clients. Sustainable Futures in the Built Environment to 2050: A Foresight Approach to Construction and Development features chapters covering: data and trends, including historical data and UK and international case studies; policies and practice related to the field; current state of scientific understanding; key challenges; key technological advances (including disruptive and systemic technological innovations); change issues and critical uncertainties; and future visions. It provides: A strong conceptual framework based on a 'Foresight' approach Discussion of the key data and trends that underpin each chapter Coverage of both construction and property development. Specially commissioned chapters by academics and practitioners. A synthesis of the main findings in the book and key insights for the future to 2050 Sustainable Futures in the Built Environment to 2050: A Foresight Approach to Construction and Development is an important book for postgraduate students and researchers, construction, real estate and property development specialists, engineers, planners, architects, foresight and futures studies specialists, and anyone involved in sustainable buildings" -- Provided by publisher.